Use of Ketorolac As An Adjuvant in Bier’s Block - Masud, Habibul Hai; Khatun, UH Shahera; Hossain, Md Mozaffer; Shoman, Mohiuddin; Alam, Md Tanveer; Mondal, Subrata Kumar (Journal of the Bangladesh Society of Anaesthesiologists, 2016)
Background: Bier’s block has been most commonly used for hand and wrist surgery of short duration. Though it reduces the potential complication of general anaesthesia, significant post-operative pain is very common just after tourniquet release. Many adjuvants eg. fentanyl, pethidine, morphine, sodi-bicarb, pancuronium, ketorolac etc. have been used so far with local anaesthetic to produce a dense block and to provide adequate post-operative analgesia. Of them Ketorolac was used very successfully as it has got less potential side-effects. This study was done to see the effect of ketorolac in Bier’s block whether and how much it provides post-operative analgesia after tourniquet release. Method: The effectiveness of combination of Lignocaine and Ketorolac as an anaesthetic solution in Bier’s block was assessed in terms of reduction of tourniquet pain, quality of anaesthesia, the time of first analgesic demanmd and the amount of total analgesic needed in post-operative 24-hours period. A total of sixty patients of ASA grade-1 and ASA grade-2 undergoing hand and wrist surgery of less than 40 minute duration were enrolled for the study. Patients in control group (Gr-L) were received forty ml of 0.5%Lignocaine and patients in trial group (Gr-LK) were received 39-ml of 0.5% Lignocaine with 1 ml (30 mg) of Ketorolac as an anaesthetic solution. Patient was observed postoperatively for 24 hours. Result: Pain was assessed in terms of VAS , and by measuring Heart rate and Blood pressure to assess sympathetic stimulation due to pain. Tourniquet pain was significantly less in Gr- LK (p<0.000). Postoperative analgesia was also significantly prolonged in Gr- LK (76.40 ± 11.78 min) than in Gr- L (27.30 ± 8.18 min). The number of total analgesic demand in postoperative 24 hours period was also significantly reduced in Gr-LK (p<0.000) Conclusion: The Lignocaine and Ketorolac mixture in Bier’s block produces significant anaesthesia and also provides adequate postoperative analgesia and causes less analgesic demand in postoperative period. These advantages ensure cost-effectiveness, shorter hospital stay and ultimately satisfactory patient outcome. JBSA 2016; 29(2): 54-61